Tinjauan Fikih Siyasah Terhadap Jihad dan Bela Negara Warga Palestina dalam Mempertahankan Kedaulatan Palestina - Iswandi, Iswandi; Lubis, Ismi Saydina (TANFIDZIY, 2023)
Jihad and State defense carried out by Palestinians have stolen the attention of the international community. Not only that, but it has given rise to a variety of interpretations. So this study aims to examine related jihad and State defense carried out by Palestinians. The method used in this study is qualitative method. The Data in this study were obtained from library literature related to this study. This study is descriptive analysis, while the data in this study is secondary data. The results of this study explain that jihad and defending the state carried out by Palestinians is not a murder under the guise of terrorists but an effort to defend the rights of citizens and human values that have been taken away by the invaders and defend the sovereignty of the state of Palestine from enemy attacks and against occupation, tyranny committed by the invaders. With reference to the fiqh Siyasah in this case the Siyasah dauliyah, jihad and defense of the state for Palestinian citizens are currently mandatory.